Keanekaragaman Pteridophyta Terestrial Di KawasanHutan Pinus Kragilan Kabupaten Magelang ProvinsiJawa Tengah - Setiawaty, Bintang Titik; , Efry Roziaty, S.Si, M.Si (2017)
Terrestrial Pteridophyta ferns that is able to grow and live on the land mainly in moist environments. The area of Pine Forest Kragilan has a fairly high humidity, making it possible to live the kind of diverse terrestrial pteridophyta. The purpose of this research is to know the diversity of terrestrial pteridophyta in pine forest area in Hamlet, Kragilan Subdistrict Pogalan Village, fern, Magelang Regency of Central Java Province. This study used a purposive sampling method in the determination of the location of the research plots. The plot of this research consists of 12 plots. The results showed in the Pine Forest area Kragilan diversity index value is low ie amounting to 0,884. This happens because a individuals spread unevenly in vegetation and just dominated by one or few types. The index of the highest diversity of types of Selaginella ornata 0,158 whereas the diversity of types of Drynaria quercifolia 0,021 is lowest.